Contents and Forewords of the SOSIOHUMANIKA Journal, Issue of November 2017 - SOSIOHUMANIKA, Editor Journal (ASPENSI in Bandung, Indonesia, 2017)
SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan. This journal, with print ISSN 1979-0112, was firstly published on May 20, 2008 in the context to commemorate One Millenium of National Awakening Day in Indonesian. The SOSIOHUMANIKA journal is published twice a year i.e. every May and November. For period 2013 to 2018, the SOSIOHUMANIKA journal has been accredited by Ditjendikti Kemdikbud RI (Directorate-General of Higher Education, Ministry of Education and Culture of the Republic of Indonesia). Since firstly issue of May 2008 to date, the SOSIOHUMANIKA journal has been published by Minda Masagi Press as a publishing house owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia; and since issue of November 2017 to date, this journal has again been managed and organized by the Lecturers of UNIPA (University of PGRI Adibuana) Surabaya, East Java, Indonesia.Â Bandung, Indonesia: 30 November 2017Andi SUWIRTAManaging Editor of SOSIOHUMANIKA Journal; and Chairperson of ASPENSI in Bandung, West Java, Indonesia.